Development of Thermoplastic Natural Rubber (TPNR) as a New Binder in Metal Injection Moulding - Omar, Mohd Afian; Hassan, Norita (Taylor's University, 2016)
Since metal injection moulding (MIM) is still new in Malaysia, therefore it is great opportunity for those who carry out the development of new binder system. Perhaps this technology can be exploited in Malaysia in future for the benefits of all industrial sectors. Developing of a new locally binder system, which is beneficial to the local industry is a great concern. Many attempts have been made in developing a new binder system which concentration is given on the cost reduction and shorten the production process. Thermoplastic natural rubber (TPNR) has a possibility as binder component because of many suitable properties it is such as low cost as locally produced, low viscosity, high decomposition temperature and easily dissolves into solvent also chemically passive. Hence, TPNR is worth to consider as a binder component.